METODE PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN TRADISIONAL - nurkholis nurkholis (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2018)
Arabic language is must to learn in pesantren, because Arabic language used in a classic books in Arabic, the actifity of worship is done daily also with the Arabic language. Pesantren is the only educational institution studying Arabic in the old of the development of Islam, even today. Arabic learning methods used by pesantren, especially traditional pesantren have been decades old using qawaid wa tarjamah method. The method does this even become a grip or characteristic of the learning process undertaken in traditional pesantren, since the majority assume that the existing learning method is the best method in the learning process, thus overriding new methods or the existence of other methods which is likely to be more effectively used in the learning of the Arabic language. There needs to be a review of the learning methods currently used by boarding schools, so that learning Arabic language can facilitate the learner or santri.